Cost-effectiveness of Pharmaceutical Interventions to Prevent Osteoporotic Fractures in Postmenopausal Women with Osteopenia - Kwon, Jin-Won (J Bone Metab, 2016)
BACKGROUND: To assess the cost-effectiveness of drug therapy to prevent osteoporotic fractures in postmenopausal women with osteopenia in Korea. METHODS: A Markov cohort simulation was conducted for lifetime with a hypothetical cohort of postmenopausal women with osteopenia and without prior fractures. They were assumed to receive calcium/vitamin D supplements only or drug therapy (i.e., raloxifene or risedronate) along with calcium/vitamin D for 5 years. The Markov model includes fracture-specific and non-fracture specific health states (i.e. breast cancer and venous thromboembolism), and all-cause death. Published literature was used to determine the model parameters. Local data were used to estimate the baseline incidence rates of fracture in those with osteopenia and the costs associated with each health state. RESULTS: From a societal perspective, the estimated incremental cost-effectiveness ratios (ICERs) for the base cases that had T-scores between -2.0 and -2.4 and began drug therapy at the age of 55, 60, or 65 years were $16,472, $6,741, and -$13,982 per quality-adjusted life year (QALY) gained, respectively. Sensitivity analyses for medication compliance, risk of death following vertebral fracture, and relaxing definition of osteopenia resulted in ICERs reached to $24,227 per QALY gained. CONCLUSIONS: ICERs for the base case and sensitivity analyses remained within the World Health Organization's willingness-to-pay threshold, which is less than per-capita gross domestic product in Korea (about $25,700). Thus, we conclude that drug therapy for osteopenia would be a cost-effective intervention, and we recommend that the Korean National Health Insurance expand its coverage to include drug therapy for osteopenia.